Design of cloud-enabled cross-platform malware analysis systems - Najafabadi, Seyed Abdolrahman Mousavian (2016)
The Internet of Thing (IoT) is already gaining momentum in the society by creating links between virtual technology and physical world. As the forecasts show, the number of devices connected to the Internet may rise to 100 billion devices by the end of the current decade. The dark side of this era, connecting everything to the Internet with lesser number security experts taking care of them. More importantly, companies are designing and implementing their platforms in the way that applications developed by third-party developers can be installed and executed seamlessly. It is to the best interest of the malicious attackers to violate the security and privacy by spreading malicious codes over a wider range of platforms including sensor nodes, smart phone, personal computer and server. This malicious activity utilizes zero-days vulnerabilities; thus the number of zero-days malware is expected to increase exponentially in the coming years. Arming security researchers with effective tools can lead to the discovery of malware in a shorter time. Hence we need an automated, cross-platform, scalable, fast, efficient and easy to use tools that can help even a novice user against the malicious attackers.